ANALISIS PENGARUH MULTIFAKTOR TERHADAP RETURN SAHAM DI INDONESIA - Sutarso Sutarso; Augustina Kurniasih; Luna Haningsih (Jurnal Manajemen, 2016)
This study aims to examine and analyze the effect of market, size, value and sharia factor on the stock return in Indonesia. Research data is monthly data for 5 years observation period from 2009 until 2013. The population in this research is all listed stock in Indonesia Stock Exchange on observation period. The sampling method used was purposive sampling. The method of analysis used multiple regresion. The results showed that market factor, firm size, BE/ME ratio and sharia factor was significantly affect stock return. Market factor was significantly positive affect stock return. Firm size was significantly positive affect stock return on small firm size and negative affect on big firm size. BE/ME ratio was significantly positive affect stock return on high BE/ME ratio and negative affect on low BE/ME ratio. Sharia factor was significantly positive affect sharia stock return and negative affect on non sharia stock return. In general, the market factor is the factor that most strongly affect stock return than any other factor.